2017
DOI: 10.1111/neup.12435
|View full text |Cite
|
Sign up to set email alerts
|

The perivascular microenvironment in Epstein–Barr virus positive primary central nervous system lymphoma: The role of programmed cell death 1 and programmed cell death ligand 1

Abstract: It has been shown that high expression of certain immune checkpoint molecules, including those of the programmed death protein 1/programmed death ligand 1 (PD-1/PD-L1) axis, can be utilized to regulate immunosuppression in the microenvironment of malignant neoplasms. For the purpose of clarifying the immune-escape mechanism of primary central nervous system lymphomas (PCNSLs), particularly in Epstein-Barr virus (EBV)-positive cases, markers for PD-1, PD-L1, tumor-associated macrophages (TAMs), and tumor-infilt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 26 publications
1
15
0
Order By: Relevance
“…Our summary of the relevant literature regarding PD-L1 expression in PCNSL is given in Table 4 [3][4][5][6]. The rate of PD-L1 expression varied, ranging from 4.1 to 97%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our summary of the relevant literature regarding PD-L1 expression in PCNSL is given in Table 4 [3][4][5][6]. The rate of PD-L1 expression varied, ranging from 4.1 to 97%.…”
Section: Discussionmentioning
confidence: 99%
“…Immune checkpoint inhibitors have thus been expected to provide novel treatment for recurrent/refractory PCNSL. A few studies have already reported the programmed death-ligand 1 (PD-L1) and PD-L2 expression on tumor cells and tumor-infiltrating immune cells in PCNSL [3][4][5][6], but the expression of these two biomarkers in peritumoral tissue remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Our summary of the relevant literature regarding PD-L1 expression in PCNSL is given in Table 4 [3][4][5][6].…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, recent clinical trials of the blockade of the programmed death protein 1 (PD-1)/PD-L1 pathway using antibodies demonstrated that this approach had significant efficacy in various malignant tumors, including primary central nervous system lymphomas. Thus, the usage of PD-1/PD-L1 pathway antibodies in CLIPPERS associated lymphoma is worth investigating [63]. Secondly, most CSF proteins originate in the blood serum regardless that a small part of them are synthesized within the CNS or the meninges [64][65][66].…”
Section: Discussionmentioning
confidence: 99%